AN IDEAL LEGAL TENDER FOR THE DIGITAL ERA - Indrawati, Fransiska Ari (Journal of Central Banking Law and Institutions, 2023)
The Covid-19 pandemic has accelerated a shift towards digital payments and altered consumer behaviour when it comes to making payments. As a result, the use of state-issued money as legal tender continues to decline in most countries. In turn, the functions and existence of legal tender has decreased. Acknowledging such facts, the purpose of this research is to examine an ideal legal tender for the digital era that can restore the legal tender function while accommodating payment innovation. This research explores legal theories on money and legal tender, as well as the characteristics of various forms of money issued by the State and the private sector, i.e., fiat money, commercial bank money, cryptocurrency, and central bank digital currency. This research concludes that an ideal legal tender for the digital era should incorporate both cash and digital currency. Under this notion, central bank digital currency might serve as the ideal legal tender for the digital era. Nonetheless, there are certain prerequisites to the issuance of such legal tender. These include at least conducting thorough interdisciplinary research and pilot projects by the central bank, establishing an adequate regulatory framework, and ensuring public acceptance of such currency as a means of payment, as well as developing the necessary infrastructure.